Pengaruh Bantuan Sosial Bersyarat Program Keluarga Harapan Terhadap Partisipasi Anak Usia Sekolah di Indonesia - Martsha, Felicia (Jurnal Pendidikan Ekonomi Indonesia, 2024)
Poverty remains a significant issue in Indonesia, particularly affecting the access of school-age children to education. One of the government's efforts to address this is through the Conditional Cash Transfer program known as Program Keluarga Harapan (PKH). This study aims to analyze the impact of PKH on the educational participation of school-age children in Indonesia. Using a Systematic Literature Review (SLR) approach, this research examines various studies on the correlation between PKH and educational participation. The findings indicate that PKH has a significant positive effect on increasing school enrollment rates, particularly at the elementary and junior high school levels, by providing financial support to underprivileged families. However, the impact on senior high school students is less pronounced, as many of them face economic pressures that compel them to enter the workforce. Other factors, such as access to technology and infrastructure, also play a role in enhancing education participation. The study concludes that while PKH contributes to reducing dropout rates, challenges remain, especially for students in remote areas and at the senior high school level. Therefore, more targeted interventions and stronger coordination with other educational support programs like Program Indonesia Pintar (PIP) and Bantuan Operasional Sekolah (BOS) are necessary to ensure comprehensive support for children's education.